What about the donor site morbidity – how invasive is the free latissimus dorsi flap? - Nikolaus Wachtel; Riccardo E. Giunta; Marc Hellweg; Maximilian Hirschmann; Constanze Kuhlmann; Nicholas Moellhoff; Denis Ehrl (Bone & Joint Open)
Aims: The free latissimus dorsi muscle (LDM) flap represents a workhorse procedure in the field of trauma and plastic surgery. However, only a small number of studies have examined this large group of patients with regard to the morbidity of flap harvest. The aim of this prospective study was therefore to objectively investigate the morbidity of a free LDM flap. Methods: A control group (n = 100) without surgery was recruited to assess the differences in strength and range of motion (ROM) in the shoulder joint with regard to handedness of patients. Additionally, in 40 patients with free LDM flap surgery, these parameters were assessed in an identical manner. Results: We measured higher values for all parameters assessing force in the shoulder joint on the dominant side of patients in the control group. Moreover, LDM flap harvest caused a significant reduction in strength in the glenohumeral joint in all functions of the LDM that were assessed, ranging from 9.0% to 13.8%. Equally, we found a significantly reduced ROM in the shoulder at the side of the flap harvest. For both parameters, this effect was diminished, when the flap harvest took place on the dominant side of the patient. Conclusion: LDM flap surgery leads to a significant impairment of the strength and ROM in the shoulder joint. Moreover, the donor morbidity must be differentiated with regard to handedness: harvest on the non-dominant side potentiates the already existing difference in strength and ROM. Conversely, if the harvest takes place on the dominant side of the patient, this difference is diminished. Cite this article: Bone Jt Open 2024;5(12):1114–1119.